2003
DOI: 10.1074/jbc.m300310200
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Light Responses in the Drosophila “Null” Phospholipase C Mutant, norpA, by the Diacylglycerol Kinase Mutant, rdgA, and by Metabolic Inhibition

Abstract: Light responses in Drosophila are reportedly abolished in severe mutants of the phospholipase C (PLC) gene, norpA. However, on establishing the whole-cell recording configuration in photoreceptors of the supposedly null allele, norpA P24 , we detected a small (ϳ15 pA) inward current that represented spontaneous light channel activity. The current decayed during ϳ20 min, after which tiny residual responses (<2 pA) were elicited by intense flashes. Both spontaneous currents and light responses appeared to be med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
6
37
0
Order By: Relevance
“…In support of this model, genetic elimination of the TRP channels partially rescued the degeneration and the LIC of the rdgA mutant (126). In addition, the LIC of PLC mutants with minimal PLC activity and with a very small residual response to light was partially rescued in double mutant combinations that also eliminated the DAG kinase (123). Although DAG surrogates activate heterologously expressed TRPL channels (110), so far activating the TRP and TRPL channels in the photoreceptor cells by exogenous application of DAG or its surrogates has proved impossible.…”
Section: Activation Of the Trp And Trpl Channels In The Photoreceptormentioning
confidence: 62%
See 3 more Smart Citations
“…In support of this model, genetic elimination of the TRP channels partially rescued the degeneration and the LIC of the rdgA mutant (126). In addition, the LIC of PLC mutants with minimal PLC activity and with a very small residual response to light was partially rescued in double mutant combinations that also eliminated the DAG kinase (123). Although DAG surrogates activate heterologously expressed TRPL channels (110), so far activating the TRP and TRPL channels in the photoreceptor cells by exogenous application of DAG or its surrogates has proved impossible.…”
Section: Activation Of the Trp And Trpl Channels In The Photoreceptormentioning
confidence: 62%
“…A more specific mechanism for activation of the TRP and TRPL channels by metabolic inhibition in the dark has been proposed by Hardie and colleagues (123). According to this mechanism, activation of the channels by metabolic inhibition is primarily because DAG kinase failed to phosphorylate DAG owing to ATP depletion.…”
Section: Activation Of the Trp And Trpl Channels In The Photoreceptormentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, it has been proposed that this is due to protein dephosphorylation, possibly of the light-sensitive channels themselves (31,39). However, in a recent study we found that activation of TRP channels by metabolic inhibition was dependent upon PLC, and we proposed that the spontaneous activation under these conditions was most likely due to failure of DAG kinase to metabolize DAG (40). Because substantial other genetic evidence is consistent with an excitatory role for DAG (reviewed in Refs.…”
mentioning
confidence: 71%